Kesiapan Karyawan dalam Menghadapi Perubahan Ditinjau dari Gaya Kepemimpinan dan Tipe Kepribadian - Narulita, Elsa; Meiyanto, Sito (Universitas Islam Indonesia, 2014)
A sensitivity of the globalization competition organization can be done by making changes. Some reaction arising from employees related changes in the organization. It is necessary to became readiness to change of employees that it can be run in accordance with the desired goals. The purpose of this study to determine the effect of transformasional leadership style and openess to experience on readiness for change of employees. The subject were employees of Company X. Characteristics of the subject in this study were at least a year became employee, at least 23 years old, 117 employees permanent employee status, and everfelt presence of organizational change. This type ofresearch uses field studies using quantitative methods. This study using three scale to measure variables that are readiness for change scale, transformasional leadership style scale and openess to experience scale. Hypotheses were tested using multiple reggression analysis. The result of this reasearch by value ofF= 13,738 and p=0,000 (p<0,01). Simultaneously, transformational leadership and opennes to experience style can predict readiness for change by 19,4 %.Keywords : Transformasional Leadership Style, Openness To Experience, Readiness For Change